CMV reactivation initiates long-term expansion and differentiation of the NK cell repertoire - Hassan, Norfarazieda; Eldershaw, Suzy; Stephens, Christine; Kinsella, Francesca; Craddock, Charles; Malladi, Ram; Zuo, Jianmin; Moss, Paul (Frontiers in Immunology, 2022)
NK cells play an important role in suppression of viral replication and are critical for effective control of persistent infections such as herpesviruses. Cytomegalovirus infection is associated with expansion of ‘adaptive-memory’ NK cells with a characteristic CD16brightCD56dim NKG2C+ phenotype but the mechanisms by which this population is maintained remain uncertain. We studied NK cell reconstitution in patients undergoing haemopoietic stem cell transplantation and related this to CMV reactivation. NK cells expanded in the early post-transplant period but then remained stable in the absence of viral reactivation. However, CMV reactivation led to a rapid and sustained 10-fold increase in NK cell number. The proportion of NKG2C-expressing cells increases on all NK subsets although the kinetics of expansion peaked at 6 months on immature CD56bright cells whilst continuing to rise on the mature CD56dim pool. Phenotypic maturation was observed by acquisition of CD57 expression. Effective control of viral reactivation was seen when the peripheral NK cell count reached 20,000/ml. These data show that short term CMV reactivation acts to reprogramme hemopoiesis to drive a sustained modulation and expansion of the NK cell pool and reveal further insight into long term regulation of the innate immune repertoire by infectious challenge.